2020
DOI: 10.31545/intagr/112269
|View full text |Cite
|
Sign up to set email alerts
|

Response of dry matter translocation and grain yield of summer maize to biodegradable film in the North China Plain

Abstract: In the North China Plain, it is a matter of urgency to explore the feasibility of using biodegradable film to replace polyethylene film. A field experiment was conducted by covering soils with polyethylene white film, biodegradable white film, biodegradable black film, while the control remained uncovered. This study analysed the effects of using different film types on summer maize dry matter accumulation and transfer, grain yield and yield components during the 2016 and 2017 summer maize growing seasons. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The fundamental way to obtain a high yield is to improve the ability of plants to produce dry matter after flowering and the ability of dry matter to transport nutrients to the grains [12,[46][47][48][49]. Ma et al [40] showed that the rate of dry matter accumulation was the highest, and the yield was the highest when the nitrogen application rate was 306.5 kg ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental way to obtain a high yield is to improve the ability of plants to produce dry matter after flowering and the ability of dry matter to transport nutrients to the grains [12,[46][47][48][49]. Ma et al [40] showed that the rate of dry matter accumulation was the highest, and the yield was the highest when the nitrogen application rate was 306.5 kg ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have clarified that the source and sink were not the dominant limiting factors for the grain filling rate of maize under appropriate N input and without abiotic stresses, but the dominant limiting factors was the dry matter (DM) accumulation and how much of assimilation distribute to each organ ( Pan et al, 2011 ; Zhu et al, 2011 ; Gasura et al, 2013 ; Shen et al, 2017 ). Additionally, previous study indicated that the assimilation source of grain filling mainly came from the current assimilation post-silking and the vegetative organ stored in the pre-silking ( Fu et al, 2011 ; Tan et al, 2020 ). In this study, although translocation efficiency of vegetative organs at the at the silking (R1) stage to the milking (R3) stages was higher than that at the R3 to maturity (R6) stages, the grain translocation efficiency was only 2.3% (R1 to R3) to 17.2% (R3 to R6) during the whole grain-filling period of maize, and with increased N input, this efficiency decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on DMP have concentrated on the effects of such factors as planting density ( Liu et al., 2011 ), sowing date ( Dou et al., 2017 ), cultivation type ( Wang et al., 2015 ; Cai et al., 2021 ) and soil fertilizer ( Dai et al., 2008 ; Wei et al., 2017 ). There have also been some studies on the effects of drought on DMP ( Jiang et al., 2018 ; Mi et al., 2018 ; Tan et al., 2019 ), but these have not generally considered roots, especially total root biomass, thus restricting in-depth understanding of relevant mechanisms.…”
Section: Introductionmentioning
confidence: 99%